The Role of Judge Mediator The Role of Judge Mediator in the Divorce Mediation Process at Masamba Religious Court North Luwu Regency - Ichsan, Nursyamsi (IJBLE Scientific Publications Community Inc., 2023)
This research aims to explain and analyse the mediation process at the Masamba Religious Court in implementing the mediation procedure and to identify the position and duties of the Mediator in resolving divorce disputes at the Masamba Religious Court, North Luwu Regency. The type of research used is descriptive quantitative and qualitative research by collecting data in the form of numbers and also by interviewing mediator judges so that data analysis can be collected. The results showed that the implementation of mediation in the Masamba Religious Court was in accordance with the procedures as stated in Supreme Court Regulation Number 1 of 2016 concerning Mediation in Court, but the effectiveness of the implementation of mediation could still not be said to be optimal, considering that the mediation process that was carried out was only a little with a minimal success rate. While the supporting factors and inhibiting factors for the success of mediation in divorce cases at the Masamba Religious Court are still not effective, due to factors that cause the failure of the mediation process in achieving peace in the jurisdiction of the Masamba Religious Court, including: First, the parties are not in good faith. Second, The conflict between the parties has been protracted and has become increasingly complicated. Third, the Competence of the Judge as a Mediator.